Analisis Hubungan antara Kepemimpinan Kewirausahaan, Transformasi Digital, dan Kinerja UMKM - Muhammad Rifai Siregar; Putri Bunga Meiliana Daulay (Jurnal Bisnis dan Kewirausahaan)
Micro, small and medium enterprises (MSMEs) play an important role in Indonesia's economic growth. This study aims to analyze the relationship between entrepreneurial leadership, digital transformation and MSME performance. Data was collected from 150 entrepreneurial respondents in various business sectors in Depok. The Structural Equation Modeling (SEM) method was used to analyze the data obtained. The results of this study reveal that entrepreneurial leadershiphas a positive and significant relationship with digital transformation. Furthermore, digital transformation also has a positive and significant relationship with MSME performance. It was found that entrepreneurial leadership has a significant direct influence on MSME performance, as well as an indirect influence through digital transformation. These findings contribute to the understanding of the importance of entrepreneurial-oriented leadership in driving digital transformation and improving MSME business performance. Managerial implications and suggestions for further research are also discussed in this study.